Follow-Up of Side Effects throughout the Entire Course of Coronavirus Vaccination - Mohanad Odeh; Ghada Nazar Al-Jussani; Abdelrahman Ashour; Husam AlNaqah; Hamza A. Hasan; Lana Sbitan; Amro Dawabsheh; Moayad Alhawi (Vaccines, 2023)
Vaccines are considered the best protective means against coronavirus infection. There is increasing interest in reporting the side effects of vaccines, especially for individuals younger than 18 years old. Accordingly, this analytical cohort study aims to report on the side effects of adult and young individuals who received vaccination within 24 h, 72 h, 5 days, and 1 week through the entire course of vaccination (ECoV). A validated online survey was used to collect information. In total, 1069 individuals were completely followed. Most individuals received the Pfizer vaccine (59.6%). Most individuals had received two doses (69.4%). Very strong and statistically significant associations with side effects (p < 0.05, Phi (Φ) > 0.25) throughout the ECoV were reported for the type of vaccine and female gender. Non-smokers reported weak statistically significant associations. Fatigue and localized pain were the most commonly reported side effect, with onset within 24 h and duration of less than 72 h. The prevalence of reported side effects was statistically significantly higher among young individuals (<18 years old) than among adults (X2 (1) =7.6, p = 0.006. Phi φ = 0.11).